(untitled) (Collection of scientific works «Modern structures of metal and wood», 2024)
Prefabricated volumetric modules with steel frame have recently become a segmentation trend for real estate, commercial multi-storey housing and office buildings projects. The obvious benefits of reducing construction time, number of site activities and related overheads as well as better quality control system compare to on-site production, 3D volumetric construction still associated with significant risks related to relatively high construction cost, potential logistics issues and lack of proven point of reference and frameworks (so-called “best practices”). Despite the fact that prefabricated modular construction known for almost a century, researches on design problems and limitations of practical implementation of volumetric modules today are still fragmentary and insufficient. Numbers of researches focused on the improving of steel frames of three-dimensional volumetric modules and their performance-based optimization, related either to the design of effective joints (e.g. self-clamp joints) or study the problems of spatial stability of multi-storey modular buildings, considering the own weight of load-bearing structures as a criterion for design efficiency. The case study illustrates that estimation of design efficiency of prefabricated volumetric modules with steel frames, besides the factors of durability and sustainability of the structure included required level of fire resistance, and the criteria of the economic efficiency of design also includes the fire protected surface area of the steel elements.